From thaw till fall: Interacting hydrology, carbon cycle, and greenhouse gas dynamics in a subarctic stream-lake continuum - Mustonen, Kaisa-Riikka; Marttila, Hannu; Lehosmaa, Kaisa; Chapman, Jack; Juutinen, Sari; Koivunen, Iina; Korkiakoski, Mika; Lohila, Annalea; Welker, Jeffrey; Jyväsjärvi, Jussi (Elsevier, 2025)
Carbon-water interaction studies between aquatic and terrestrial ecosystems are especially needed today in Arctic and Boreal regions, as they are facing drastic warming and precipitation shifts. Despite the importance of streams in the carbon cycle, northern stream-based studies are scarce, owing to a lack of measurements throughout the north, and possibly skewing global greenhouse gas estimates. We used a combination of multiscale measurements to quantify water sources (H2O isotope proxies), carbon availability (dissolved in/organic carbon concentrations) and quality (water absorbance, SUVA254 –index), microbial community structure (16S rRNA sequencing), and carbon dioxide (CO2) and methane (CH4) fluxes and concentrations. Our study site comprises a groundwater-influenced and peatland-dominated second-order stream, along with its adjacent lake inlet located in Northern Finland. Sampling was conducted three times during the summer of 2019 at 21 locations along the stream-lake continuum. Temporal and spatial shifts in water sources altered carbon characteristics, with CH4 concentrations being the key environmental factor shaping the microbial communities, overriding the influence of dissolved organic carbon amount and quality. The prevalence of methanotrophic bacteria highlighted the importance of CH4 as a carbon source and the methanotrophic groups as drivers of the CH4/CO2 source-sink attributes of subarctic stream systems. Our results highlight the value of integrated hydrological, biogeochemical, and microbiological measures to resolve the biocomplexity of carbon-water interactions in northern headwater catchments.